Feed the Future Innovation Lab for Genomics to Improve Poultry: a holistic approach to improve indigenous chicken production focusing on resilience to Newcastle disease - Zhou, Huaijun; Baltenweck, Isabelle; Dekkers, J.; Gallardo, R.; Kayang, B.B.; Kelly, T.; Msoffe, P.L.M.; Muhairwa, A.; Mushi, J.; Naaziee, A.; Otsyina, H.R.; Ouma, Emily A.; et al. (Informa UK Limited, 2024)
Small-scale poultry production in Africa plays a significant role in alleviating malnutrition and poverty in rural communities. Global climate change and infectious poultry disease such as Newcastle disease (ND) have had tremendous negative impact on poultry production and health due to limited biosecurity, cold chain, and inadequate extension service. Genetic selection for enhanced resistance to ND virus (NDV) offers a promising complementary approach to vaccination and biosecurity in addressing constraints in village production systems. The Feed the Future Innovation Lab for Genomics to Improve Poultry (GIP IL) has led an effort on the identification of genetic markers, genes and signalling pathways associated with enhanced resistance to NDV by conducting NDV challenging experiments in diverse inbred, commercial, and African indigenous chickens. The GIP IL developed a comprehensive genetic selection platform focusing on improved survival time and reduced virus shedding in the face of NDV infection and on enhanced growth rate and egg production. The programme applied the platform for genetic selection and breeding of indigenous chickens through velogenic NDV natural exposure trials. To improve our understanding of the epidemiology of NDV in Africa, we characterised circulating strains of the virus in Ghana and Tanzania and identified NDV risk factors among local chickens. These data contribute to a body of knowledge useful for guiding disease control efforts, informing vaccine strategies, enhancing biosecurity, and contributing to our overall understanding of NDV dynamics. To gauge the demand for genetically improved indigenous poultry lines, we undertook assessments of the poultry value chain and conducted choice experiments in Ghana and Tanzania, and the findings suggest that both ND enhanced resistance attribute and other productivity attributes of chicken such as egg production and body weight gain are important for a breeding programme.